2018
DOI: 10.1021/acs.orglett.7b03950
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a Crystalline, Shelf-Stable Reagent for the Synthesis of Sulfur(VI) Fluorides

Abstract: The design, synthesis, and application of [4-(acetylamino)phenyl]imidodisulfuryl difluoride (AISF), a shelf-stable, crystalline reagent for the synthesis of sulfur(VI) fluorides, is described. The utility of AISF is demonstrated in the synthesis of a diverse array of aryl fluorosulfates and sulfamoyl fluorides under mild conditions. Additionally, a single-step preparation of AISF was developed that installed the bis(fluorosulfonyl)imide group on acetanilide utilizing an oxidative C-H functionalization protocol. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 35 publications
0
96
0
Order By: Relevance
“…[44] Considering the feasibility and safety of practical operation and the characteristic of small reaction scale of on-DNA synthesis, we chose solid reagents [4-(acetylamino)phenyl] imidodisulfuryl difluoride (AISF) [45] and fluorosulfuryl imidazolium salt [46] that had recently developed by scientists at Bio-Duro/Pfizer, and the Dong group, respectively, for the on-DNA synthesis of ArOSO 2 F. The results of comparative trials suggested that AISF was a more suitable reagent for the current on-DNA -SO 2 F decoration (see Table S1, Supporting Information). [44] Considering the feasibility and safety of practical operation and the characteristic of small reaction scale of on-DNA synthesis, we chose solid reagents [4-(acetylamino)phenyl] imidodisulfuryl difluoride (AISF) [45] and fluorosulfuryl imidazolium salt [46] that had recently developed by scientists at Bio-Duro/Pfizer, and the Dong group, respectively, for the on-DNA synthesis of ArOSO 2 F. The results of comparative trials suggested that AISF was a more suitable reagent for the current on-DNA -SO 2 F decoration (see Table S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[44] Considering the feasibility and safety of practical operation and the characteristic of small reaction scale of on-DNA synthesis, we chose solid reagents [4-(acetylamino)phenyl] imidodisulfuryl difluoride (AISF) [45] and fluorosulfuryl imidazolium salt [46] that had recently developed by scientists at Bio-Duro/Pfizer, and the Dong group, respectively, for the on-DNA synthesis of ArOSO 2 F. The results of comparative trials suggested that AISF was a more suitable reagent for the current on-DNA -SO 2 F decoration (see Table S1, Supporting Information). [44] Considering the feasibility and safety of practical operation and the characteristic of small reaction scale of on-DNA synthesis, we chose solid reagents [4-(acetylamino)phenyl] imidodisulfuryl difluoride (AISF) [45] and fluorosulfuryl imidazolium salt [46] that had recently developed by scientists at Bio-Duro/Pfizer, and the Dong group, respectively, for the on-DNA synthesis of ArOSO 2 F. The results of comparative trials suggested that AISF was a more suitable reagent for the current on-DNA -SO 2 F decoration (see Table S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the reaction with bromomethyl-benzenesulfonyl fluorides will result in agents as reported in Figure 1B. The synthesis of aryl-fluoro sulfates followed a recently developed approach that takes advantage of the [4-(acetylamino)phenyl]imidodisulfuryl difluoride (AISF) 37 reagent for the insertion of the fluoro sulfate functional group into Tyr or homo-Tyr ( Figure 1C). Alternatively, substituted or unsubstituted phenol carboxylic acids can be introduced in the side chains of Dap, Dab, Orn, or Lys, and subsequently the phenols can be converted to their corresponding aryl-fluoro sulfates ( Figure 1D) using the same procedure as reported in Figure 1C.…”
Section: Synthesis Of Peptide Mimetics Containing Aryl-mentioning
confidence: 99%
“…Over the past 5 y, we (1,5,8,56) and others (12,(57)(58)(59)(60) have found a collection of efficient methods to synthesize SuFExable compounds from either simple or complex organic molecules using highly connective SuFEx core electrophiles (e.g., SO 2 F 2 , O = SF 4 , CH 2 = CHSO 2 F). Collective work within the Sharpless laboratory continues to build a library of SuFExable small modules.…”
Section: Significancementioning
confidence: 99%